LEGAL PROTECTION DISASTER RESPONSE VOLUNTEERS (PERKA study No. 17 of 2011 regarding Disaster Management Volunteer Guidelines) - Arti Novelia Trisnawati; Dina Sunyowati; Setya Heksama (Universitas Airlangga, 2023)
The policy on volunteers for disaster management has been in place since the publication of Regulation of theHead of the National Disaster Management Agency Number 17 of 2011, but along with the development ofvolunteer activities and volunteer organizations in supporting disaster management activities in Indonesia, theproblems faced by volunteers are increasingly complex, starting from rights issues. and obligations to legalprotection of volunteers. This research aims to analyze the legal principles and theories that apply to theRegulation of the Head of the National Disaster Management Agency Number 17 of 2011 concerning Guidelinesfor Volunteers for Disaster Management, analyze the Regulation of the Head of the National Disaster ManagementAgency (PERKA BNPB) Number 17 of 2011 concerning guidelines for disaster management volunteers that havethe potential to cause problems orPolicy Potential Problem as well asPolicy Application Problem or applicationof the policy. The method used is a quantitative descriptive approach socio legal research and using data collectiontechniques in the form of Likert questionnaires and in-depth interviews, the results of the questionnaires show thatsome disaster management volunteers have problems understanding their rights and obligations as well as theimplementation of disaster management volunteer guidelines which are still not optimal, so it can be concludedthat Regulation of the Head of the National Disaster Management Agency No. 17 of 2011 still has the potentialtoPolicy Potential Problem Policy Application Problem.